AB0196 Do patients with early ra and vitamin d deficiency have increased disease activity at the time of diagnosis?. (23rd January 2014) - Salman Monte, T. C.; Pérez-Ruiz, J.; Almirall, M.; Sánchez, S.; Lisbona, M.
Abstract : Objectives: Asses if there are differences in clinical and biological markers of disease activity in patients with early RA depending on they have vitamin D deficiency or not. Evaluate the correlation between vitamin D deficiency and disease activity. Methods: Observational, retrospective study of a cohort of patients with early RA (ACR 1987 classification criteria, with a duration of symptoms less than one year and treatment naïve except for NSAIDs and/or glucocorticoids) who had determination of 25-OH Vitamin D serum levels prior to initiation treatment with a DMARD. Patients had been taken vitamin D supplements were excluded. For each patient demographic (age, gender), clinical (FR U/ml, ACPA U/ml, smoking yes/no, BMI, DAS 28, SDAI, visual pain analog scale VAS 0-10 cm, patient global assessment PGA 0-10cm, HAQ, glucocorticoid treatment) and laboratory (ESR mm/h, CRP mg/dl, 25-OH Vitamin D serum levels ng/ml, PTH (pg/ml) ) parameters were collected. The data were analyzed using SPSS 15.0. Results: : A total of 96 early RA patients (64 women) were included in the study. 54 (56.2%) had vitamin D deficiency (≤ 20 ng/ml) and 42 patients (44.8%) had serum vitamin D level > 20 ng/ml. 83.3 % of the patients had <30 ng/ml serum vitamin D level (vitamin D insufficiency). There were no statistically significant differences in demographic and clinical characteristics, functional disability and some biological parameters of activity between the two groups of patients according to the presence or not of vitamin D deficiency, except that patients with vitamin D deficiency showed lower CRP, RF and ACPA levels (Table 1 ). No statistically significant correlation between vitamin D deficiency and disease activity (DAS 28, SDAI, ESR) and functional disability (HAQ) was observed. However, vitamin D deficiency was correlated with lower CRP values (r = 0.30, p = 0.002) (Table 2). It was also observed a trend to higher mean VAS pain and PGA in the group of patients with vitamin D deficiency. Conclusions: The prevalence of vitamin D deficiency in our cohort of early RA patients was 56.2%, similar to the data found in other studies (1). No significant correlation was found between vitamin D deficiency and increased disease activity in our series of patients with RA. However, patients with vitamin D deficiency had lower CRP levels although they had more pain and worse disease assessment (PGA). Acknowledgements: Acknowledgments Sergi Mojal. AMIB. Disclosure of Interest: None Declared